Amended Calculation of Solar Heat Gain Coefficient Based on the Escape of Incident Solar Radiation - Shunyao Lu; Dongfang Yang; Xiaoqing Huang; Tao Chen; Zhengzhi Wang (Energies)
The solar heat gain is an important component of building cooling load, and its magnitude affects building energy consumption directly. In buildings with glass curtain walls, the window to wall rate is close to 1, so the amount of solar heat gain is huge, which directly determines the energy consumption level of a building’s air conditioning system. In fact, incident solar radiation can escape to the exterior through the transparent envelope, which cannot be ignored in buildings with glass curtain walls. This will cause changes in solar heat gain, so the solar heat gain coefficient (SHGC) needs to be corrected. In this paper, the heat transfer process of solar radiation in window shading systems is analyzed, and an amended calculation model for the SHGC is established. Multiple forms of windows and shading systems are selected and their SHGC-amended factor for rooms with different orientations under different standard calculation conditions in various countries is calculated. As the number of glass layers increases, the transmittance of the window gradually decreases, the reflectance and absorbance gradually increase, and the SHGC value decreases. The SHGC-amended factor decreases with an increasing escape rate, and the two can be approximated as a linear correlation. The weakening effect of shading on the solar heat gain of the buildings is overestimated. The SHGC-amended factor proposed in this paper can calculate building solar heat gain more accurately.